Immunomodulating Hydrogels as Stealth Platform for Drug Delivery Applications - Zahra Rezaei; Dilara Yilmaz-Aykut; Fatima Mumtaza Tourk; Nicole Bassous; Margot Barroso-Zuppa; Asif Iqbal Shawl; Syed Salman Ashraf; Huseyin Avci; Shabir Hassan (MDPI AG, 2022)
Non-targeted persistent immune activation or suppression by different drug delivery platforms can cause adverse and chronic physiological effects including cancer and arthritis. Therefore, non-toxic materials that do not trigger an immunogenic response during delivery are crucial for safe and effective in vivo treatment. Hydrogels are excellent candidates that can be engineered to control immune responses by modulating biomolecule release/adsorption, improving regeneration of lymphoid tissues, and enhancing function during antigen presentation. This review discusses the aspects of hydrogel-based systems used as drug delivery platforms for various diseases. A detailed investigation on different immunomodulation strategies for various delivery options and deliberate upon the outlook of such drug delivery platforms are conducted.